2013
DOI: 10.1177/0268355513497362
|View full text |Cite
|
Sign up to set email alerts
|

Is the treatment of the small saphenous veins with foam sclerotherapy at risk of deep vein thrombosis?

Abstract: Deep vein thrombosis after foam sclerotherapy of the small saphenous vein are very rare. Only 0.6% medial gastrocnemius veins thrombosis occurred in symptomatic patients. However, the anatomical pattern of the small saphenous vein should be taken into account and patients with medial gastrocnemius veins perforators and the small saphenous vein connected directly into the popliteal vein should be checked by Duplex ultrasound one or two weeks after the procedure. Recommendations based on our everyday practice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
(30 reference statements)
4
14
0
1
Order By: Relevance
“…After full text evaluation, 62 studies discussing sclerotherapy management of varicose veins were included involving 3689 patients (CDFS 789 and FS 2900). 11,16,19,20,2884 Of these, there were 48 studies for UGFS and 15 studies for CDFS. There was only one randomized controlled trial directly comparing these two alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…After full text evaluation, 62 studies discussing sclerotherapy management of varicose veins were included involving 3689 patients (CDFS 789 and FS 2900). 11,16,19,20,2884 Of these, there were 48 studies for UGFS and 15 studies for CDFS. There was only one randomized controlled trial directly comparing these two alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown significantly lower rates of DVO after sclerotherapy as revealed by routine DUS ranging from 1.1% to 3.2%. [9][10][11][12] However, these studies focused on a mixed population of patients who underwent less tributary treatment and more ablation of GSV or SSV trunks using liquid or foam sclerotherapy with a different DUS interval. Thus, a control DUS 8 to 30 days after foam sclerotherapy of incompetent GSV and SSV trunks may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The reported incidence of serious complications is very low, and the rate of symptomatic deep vein thrombosis (DVT) and pulmonary embolism (PE) appears to be <1%. 6 However, asymptomatic (silent) DVT is found more often (up to 3.2%) using routine duplex ultrasound scan (DUS), [9][10][11][12] but its clinical relevance is not well established. Furthermore, fewer data are available on the prevalence of superficial vein thrombosis (SVT), silent occlusion of preserved great saphenous (GSV), or small saphenous (SSV) veins after UGFS.…”
Section: Introductionmentioning
confidence: 99%
“…Complications and serious perioperative adverse events such as deep vein thrombosis (DVT) and thromboembolism (TE) are rarely reported in UGFS, but their frequency may increase with the treatment of, e. g., incompetent perforator veins [16]. UGFS patients are at low risk especially for nerve injury.…”
Section: Ultrasound-guided Foam Sclerotherapyan Overviewmentioning
confidence: 99%
“…Generally, UGFS can be regarded as a safe technique to treat incompetent VV with very few serious adverse events and acceptable minor complications in terms of frequency, severity and duration. Severe complications, such as DVT and PE, have been reported occasionally, but incidence in symptomatic patients typically does not exceed 1 % [6,40] whereby differences in the anatomical pattern and the type of affected incompetent vein may play a role [16,41]. In the 3 studies specifically investigating outcomes of UGFS in the treatment of RVV (total of 436 patients) gastrocnemius vein thrombosis occurred in 0.2 % of cases reported by Pavei ▶Table 2 Anatomical success of UGFS treatment specifically in patients with RVV.…”
Section: Progression Of Disease (Pd)mentioning
confidence: 99%